d x d y + x y = ln x × y 2
Let y = f ( x ) be a solution to the above differential equation such that f ( 1 ) = 1 .
Given that f ( x ) = x b ( c − ln d x ) a for positive real numbers a , b , c and d , find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I'm quite surprised that none of the posted solutions mention that this is a standard Bernoulli differential equation (this being the n = 2 case).
Log in to reply
There is nothing to be surprised. If required,without commenting about your surprise,you should directly post a solution.
Log in to reply
I didn't post a solution since there's a standard well-known method for solving Bernoulli differential equations (if solutions exist) :
For the Bernoulli equation with parameter n , you multiply both sides by ( 1 − n ) y − n and then make the substitutions V = y 1 − n with d x d V = ( 1 − n ) y − n d x d y and the differential equation reduces to a first order linear differential equation in V which is then solved by integrating factor method .
Log in to reply
@Prasun Biswas – Actually my solution did use the I.F, I just didn't mention the name Bernoulli.
d
x
d
y
+
x
y
=
ln
x
⋅
y
2
Dividing by
y
2
y
2
1
d
x
d
y
+
x
y
1
=
ln
x
y
1
=
t
→
y
2
1
d
x
d
y
=
d
x
−
d
t
The differential transforms into,
d
x
d
t
−
x
t
=
−
ln
x
This is a linear differential equation of the form
d
x
d
t
+
P
t
=
Q
Integrating factor =
e
∫
P
d
x
=
e
∫
x
−
d
x
=
x
1
Multiplying by
x
1
on both sides,
x
d
x
d
t
−
x
2
t
=
x
−
ln
x
d
x
d
(
x
t
)
=
x
−
ln
x
∫
d
(
x
t
)
=
∫
x
−
ln
x
d
x
+
2
c
Integrating both sides,
x
2
t
=
c
−
ln
2
x
x
y
2
=
c
−
ln
2
x
Since,
f
(
1
)
=
1
1
⋅
1
2
=
c
−
0
→
c
=
2
∴
y
=
x
(
2
−
ln
2
x
)
2
Comparing, a = 2 , b = 1, c = 2, d = 2
a
+
b
+
c
+
d
=
2
+
2
+
2
+
1
=
7
First, rewrite the original equation as, x d x d y + y = x y 2 ln ( x ) in which can be written as, d x d ( x y ) = x y 2 ln ( x ) Define u = x y , then we have a separable differential equation, d x d u = x u 2 ln ( x ) Since ∫ x ln ( x ) d x = 2 1 ln 2 ( x ) + C , then we have u ( x ) = − 2 1 ln 2 ( x ) + C 1 or, in original variable, y ( x ) = − x ( 2 1 ln 2 ( x ) + C ) 1 The condition y ( 1 ) = 1 imply C = − 1 . Hence, we have y ( x ) = x ( 2 − ln 2 ( x ) ) 2
So, a + b + c + d = 7 .
Problem Loading...
Note Loading...
Set Loading...
Let's start with the given differential equation:
d x d y + x y = ln ( x ) y 2
Now, divide both sides by − y − 2 to get:
− y − 2 d x d y − x y 1 = − l n ( x )
Let w = y − 1 . This means that d x d w = − y − 2 d x d y . Substituting this in gets us:
d x d w − x w = − l n ( x )
Multiply both sides by x to get:
x d x d w − w = − x l n ( x )
Now comes the most crucial step - Let w = u x for some parameterization u . This means that d x d w = u + x d x d u . Now substituting this in gets us:
u x + x 2 d x d u − u x = − x l n ( x ) d x d u = x − l n ( x )
Now this looks like something we know how to deal with!
∫ d u = ∫ x − ln ( x ) d x
Let v = l n ( x ) . Then d v = x 1 d x , and so we have:
∫ d u = ∫ − v d v
u = 2 − 1 v 2 + k
u = 2 − 1 l n 2 ( x ) + k
From the above information we know that u = x w = x y 1 , so:
x y 1 = 2 − 1 l n 2 ( x ) + k
And finally:
y = k x − 2 1 x l n 2 ( x ) 1
In order to get the equation in the form that the question asked for, multiply the RHS by 2 2 and pull out the x in the denominator in order to get:
y = f ( x ) = x ( 2 k − l n 2 ( x ) ) 2
Now for the Initial Value piece of the problem. We know that f ( 1 ) = 1 , and that
f ( 1 ) = 2 k 2
so 2 k = 2 , and we can FINALLY write f ( x ) as
f ( x ) = x ( 2 − l n 2 ( x ) ) 2
and so a + b + c + d = 2 + 1 + 2 + 2 = 7 .